2022
DOI: 10.3390/molecules27103204
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Hydrolysable Tannins and Lipid Vesicles from Escherichia coli with Isothermal Titration Calorimetry

Abstract: Isothermal titration calorimetry (ITC) was used to study the interactions between hydrolysable tannins (HTs) and lipid vesicles prepared from a phospholipid extract of Escherichia coli (E. coli). A group of 24 structurally different HTs was selected, and structural differences affecting their affinities to interact with lipid vesicles in aqueous buffered media were identified. In general, the interactions between HTs and lipid vesicles were exothermic in nature, and ITC as a technique functioned well in the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 42 publications
3
31
1
Order By: Relevance
“…ITC has been quite intensively applied to study the interactions of peptides or proteins with model and natural membrane phospholipids [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. However, so far, there seems to be only one ITC study on polyphenol–lipid interactions focusing on the interactions between HTs and lipid vesicles prepared from the total phospholipid extract of Escherichia coli [ 29 ]. In this study, the interactions between tannins and lipids were found to be exothermic (heat released), and the strongest interaction was observed for rugosin G up to – 160 kJ/mol when 0.1 mM tannin solution was titrated into 2 mM lipid solution as shown in Figure 3 B [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…ITC has been quite intensively applied to study the interactions of peptides or proteins with model and natural membrane phospholipids [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. However, so far, there seems to be only one ITC study on polyphenol–lipid interactions focusing on the interactions between HTs and lipid vesicles prepared from the total phospholipid extract of Escherichia coli [ 29 ]. In this study, the interactions between tannins and lipids were found to be exothermic (heat released), and the strongest interaction was observed for rugosin G up to – 160 kJ/mol when 0.1 mM tannin solution was titrated into 2 mM lipid solution as shown in Figure 3 B [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a typical ITC measurement, the lipid solution is placed in the sample cell of the calorimeter, and the polyphenol solution is titrated into the lipid incrementally [ 29 , 54 , 64 ]. The control measurements are important for excluding the other heats present.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations